Students’ Difficulties in Writing Thesis Background - Thahirah Thahirah; Maemuna Muhayyang; Amra Ariyani (Program Studi Pendidikan Bahasa Inggris FBS UNM, 2023)
The aim of this research is to find out the students’ difficulties, the most common difficulties faced by students, and how the students overcome the difficulties in writing thesis background. The participants of this research were eight students in the English education study program of UNM in the academic year 2018. The method of this research was a descriptive qualitative design with interviews and documents as the instrument for collecting data. The result of this research showed three points as follows: 1) The difficulties encountered by the students of the English Education study program at Universitas Negeri Makassar are: a) writing and organizing ideas, b) Novelty, c) Importance, d) lack of vocabulary and e) Grammar. 2) The most common difficulties encountered by the students are writing and organizing ideas. This difficulty arises because there is still a lack of ability to write and understand what should be included in the background. 3) Their way to solve the difficulties they faced when writing a thesis background was three events namely; a) working independently, b) developing or joining a community of practice, and c) working with the supervisor.